Exchange bias and exchange spring effects in Fe/CrN bilayers. (6th January 2020) - Alam, Khan; Meng, Keng-Yuan; Ponce-Pérez, Rodrigo; Cocoletzi, Gregorio H; Takeuchi, Noboru; Foley, Andrew; Yang, Fengyuan; Smith, Arthur R
Abstract: We studied exchange bias and exchange spring effects in magnetic bilayer thin films of Fe and CrN grown by molecular beam epitaxy. First, the relationships between exchange bias, coercivity, and blocking temperature and the Fe and CrN layers thicknesses are studied. Second, the exchange spring effect is observed and studied in all samples. The exchange spring breaks free at critical applied field strengths while creating planar domain walls at lower applied fields. First-principles calculations are performed to understand the magnetic interactions between the Fe and CrN layers at their interfaces. The calculations are key to understanding the experimental observations.